Stearic acid grafted chitosan/epoxy blend surface coating for prolonged protection of mild steel in saline environment. Issue 20 (18th October 2019) - K O, Shamsheera; Prasad, Anupama R; Garvasis, Julia; Basheer, Sabeel M; Joseph, Abraham
Abstract: Chitosan (CS) is a promising candidate for green anticorrosive coating owing to its film forming nature, complexation with metals, biocompatibility, and varied surface functionalization. This paper illustrates the surface properties of chitosan film which is modified by grafting with stearic acid via a water-soluble coupling agent, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC). The interaction between chitosan and stearic acid were investigated theoretically by Gaussian 09 package. The purified co polymeric films so formed were characterized by FTIR-ATR, NMR, XRD, TGA, CHNSO, SEM, AFM and EDX techniques. Stearic acid grafted CS film was developed on mild steel surface via dip coating technique and investigated for its corrosion resistance in 3.5% NaCl via electrochemical techniques. EIS measurements and potentiodynamic polarization studies have proven that the grafted CS when blended with epoxy resin offers better corrosion protection to mild steel in saline environment. The coating offers prolonged protection for the metal surface with enhanced barrier properties and hydrophobic nature.